Qualitative Research on Youths’ Social Media Use: A review of the literature - Mardi Schmeichel; Hilary E Hughes; Mel Kutner (Middle Grades Review, 2018)
In this article we explore how educational researchers report empirical qualitative research about young people’s social media use. We frame the overall study with an understanding that social media sites contribute to the production of neoliberal subjects, and we draw on Foucauldian discourse theories and the understanding that how researchers explain topics and concepts produces particular ways of thinking about the world while excluding others. Findings include that 1) there is an absence of attention to the structure and function of social media platforms; 2) adolescents are positioned in problematic, developmental ways, and 3) the over-representation of girls and young women in these studies contributes to the feminization of problems on social media. We conclude by calling for future research that can serve as a robust resource for exploring adolescents’ social media use in more productive, nuanced ways.
Keywords: social media; adolescents; neoliberalism; discourse analysis